2022
DOI: 10.1530/eje-22-0034
|View full text |Cite
|
Sign up to set email alerts
|

Low IGF1 and high IGFBP1 predict diabetes onset in prediabetic patients

Abstract: Some individuals develop T2DM despite significant metabolic improvements through lifestyle intervention. We tested the hypotheses that IGF1 and its binding proteins 1 and 2 a) predict the onset of T2DM in prediabetes patients, b) determine the capacity for metabolic regeneration. Design We measured fasting serum IGF1, IGFBP1 and IGFBP2 in 3 randomized controlled lifestyle intervention trials, covering at least 1 year of intervention period and 1 year of additional follow-up. Methods Within a sample of 414… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 46 publications
6
11
0
Order By: Relevance
“…Consistent with our study, significantly decreased serum IGF1 and decreased renal Igf1 RNA levels were found in db/db mice with DKD in a previous study ( Segev et al, 2007 ). A lifestyle intervention trial also found that low IGF1 levels predicted DM onset in patients with prediabetes ( Meyer et al, 2022 ). However, unlike our study, which demonstrated low IGF1 expression in DKD patients, some studies have reported that IGF expression increases with DKD progression ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our study, significantly decreased serum IGF1 and decreased renal Igf1 RNA levels were found in db/db mice with DKD in a previous study ( Segev et al, 2007 ). A lifestyle intervention trial also found that low IGF1 levels predicted DM onset in patients with prediabetes ( Meyer et al, 2022 ). However, unlike our study, which demonstrated low IGF1 expression in DKD patients, some studies have reported that IGF expression increases with DKD progression ( Dong et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP1 is a multifunctional protein that regulates the biological effects of insulin-like growth factors, regulates glucose and lipid metabolism, and participates in apoptosis and other biological processes [31]. When insulin levels decrease, IGFBP1 expression increases, leading to a decrease in the release of glucose; this consequently affects lipid metabolism and promotes fatty acid oxidation [32]. Kim et al reported that overproduction of ITIH1 after loss of Gα13 in the liver exacerbates systemic insulin resistance in mice [33].Moreover, the expression levels of ITIH3 (log 2 FC = 10.89) and ITIH2 (log 2 FC = 10.79) were significantly upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, using publicly available repositories of gene-based associations in the UK Biobank data, we found that rare missense variants from MSR1 (associated with transferrin glycosylation) were also associated with blood levels of insulin-like growth factor 1 (IGF1). IGF1 is a hormone with significant structural and functional similarities to insulin: lower levels of IGF1 are associated with higher risk of Type 1 and 2 diabetes mellitus 41,42 . Recently, a rare deleterious missense variant in IGF1 receptor (IGF1R) was found to be significantly associated with Type 2 diabetes in UK Biobank, further corroborating the link between IGF1 and diabetes 43 .…”
Section: Discussionmentioning
confidence: 99%